Investigation of the Fit of Computer-based Parametric Garment Prototypes (Journal of Fiber Bioengineering and Informatics, 2013)
The paper presents part of a comprehensive and complex investigation in the field of computer designand 3D garment simulation within which it investigates developed computer-based parametric prototypeof a men's suit and whether it is suitable for computer adaptation according to measurements of differentbody characteristics. The investigation was conducted by segments. It was necessary to do tests andmeasurements using innovative computing technologies and appropriate measuring equipments. Usingthe 2D/3D CAD system for the preparation of garment construction, a 2D pattern was developed forthe purpose of computer grading for selected sets of sizes according to different figures and statures.The scanning data process was performed through using a 3D laser scanner and a computer analysiswas made with anthropometric measurements of the body on a sample of male subjects of differentanthropometric body characteristics. The most complex part of the research was finding mathematicalexpressions and comprehensive development of a men's suit model with the aim of translating 2D patternparts from vector into parametric format, which allows simultaneous changes in several correspondingsegments of pattern pieces.
Keywords: Computer Garment Construction; CAD System; 3D Simulation; Made-to-measure